(MC2)2: criteria, requirements and a software prototype for Cloud infrastructure decisions. (31st August 2011) - Menzel, Michael; Schönherr, Marten; Tai, Stefan; Sicilia, Miguel‐Angel
SUMMARY Cloud computing is a disruptive technology, representing a new model for information technology solution engineering and management that promises to introduce significant cost savings and other benefits. The adoption of Cloud computing requires a detailed comparison of infrastructure alternatives, taking a number of aspects into careful consideration. Existing methods of evaluation, however, limit decision‐making to the relative costs of Cloud computing, but do not take a broader range of criteria into account. The Multi‐Criteria Comparison Method for Cloud Computing (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3m7785j5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(MC2)2</alternatives>) offers a multi‐criteria‐based decision framework that can be applied to Cloud computing. The framework allows organizations to create evaluation methods that help to determine what infrastructure best suits their needs by evaluating and ranking infrastructure alternatives using multiple criteria derived from a comprehensive criteria catalog. Therefore, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3m7785m8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(MC2)2</alternatives> offers a way to differentiate infrastructures not only by costs but also in terms of benefits, opportunities and risks. <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3m7785cd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(MC2)2</alternatives> can be adapted to facilitate a wide array of decision‐making scenarios within the domain of information technology infrastructures, depending on the criteria selected to support the framework. The software prototype presented in this paper creates an interface to decision‐makers that makes the framework more usable for Cloud infrastructure decisions in practice. Copyright © 2011 John Wiley & Sons, Ltd.